Sustainable Tourism in Southeast Asia: Balancing Economic Growth, Employment, and Carbon Emissions Through Evidence-Based Strategies - Aini, Yulinda Nurul (Jurnal Kepariwisataan Indonesia: Jurnal Penelitian dan Pengembangan Kepariwisataan Indonesia, 2024)
Tourism, one of the world's fastest-growing industries, can boost GDP and create jobs. Southeast Asia ranks third among the thirteen tourism markets. 125.78 million visitors are expected annually. This industry contributes 12% of GDP and 4% of employment. However, tourism and related services have increased global carbon emissions from transportation, electricity, and housing. Since the UN's SDGs encourage tourism as a green growth industry to reduce carbon emissions, the ASEAN Socio-cultural Community (ASCC) Blueprint 2025 promotes environmentally sustainable cities. Consequently, this study uses panel data regression to examine tourism's effects on economic growth, employment, and carbon emissions. The findings can then provide a numeric assessment of the SDGs and the ASCC Blueprint 2025. This study uses 2002–2019 World Bank data from 11 Southeast Asian nations. The results reveal that GDP, employment, and carbon emissions are best modelled by the random effect and fixed effect models, respectively. We also find that tourism positively impacts GDP (p<0.001), employment (p<0.008), and carbon emissions (p<0.001). These models estimate that 22,000 international tourists will increase employment by 6.14% and generate $894 million in revenue. However, it will increase annual carbon emissions by 27 million. These findings suggest Southeast Asian governments, policymakers, and others should promote sustainable eco-tourism to boost economic development and green job creation by reducing carbon emissions. The government should incentivize the local community, as the tourism industry's primary actors, to promote awareness about these programs by implementing low-carbon technology and eco-friendly energy sources.